SOSIALISASI DAMPAK KECERDASAN BUATAN DALAM MENINGKATKAN PEMBELAJARAN DI PONDOK PESANTREN NAFIDATUNNAJAH - Artaningsih, Eka Yuni Titik (JAMAIKA: JURNAL ABDI MASYARAKAT, 2026)
The development of artificial intelligence has brought significant changes to the education sector; however, understanding and utilization within Islamic boarding schools still face challenges, including limited technological literacy and concerns regarding negative impacts of digital technology. This activity aims to disseminate knowledge about the impact of artificial intelligence and to enhance the understanding of educators and students regarding its potential application in the learning process at Pondok Pesantren Nafidatunnajah. The method employed includes interactive material delivery, discussions, and demonstrations of artificial intelligence applications to support adaptive, effective, and contextually relevant learning activities. The results indicate an improvement in participants’ understanding of artificial intelligence concepts, its benefits in enhancing learning quality, and awareness of ethical considerations and usage limitations. Participants also demonstrated positive responses and interest in integrating this technology as a supporting learning medium while maintaining Islamic values and the unique character of the boarding school. In conclusion, the socialization of artificial intelligence serves as a strategic step in improving the quality of learning in Islamic boarding schools through appropriate, responsible, and competency-oriented technological utilization.   Keywords: Artificial Intelligence; AI Learning; Impact of AI Technology